Research and Application of a Reinforced Concrete Simplified Model - Haipeng Jia; Shuaikang Tian (Advances in Civil Engineering)
To accurately and efficiently carry out numerical calculations for blasting demolition projects, based on the basic principles of engineering mechanics, a simplified concrete model is established. This model represents the postpeak behavior of concrete in compression and the peak behavior in traction. Based on the mechanical properties of steel and concrete materials, a new reinforced concrete model is proposed. The proposed reinforced concrete model has been implemented in the computer program LS-DYNA and used to simulate a real blasting demolition. The result shows that this model can accurately reflect the collapse and movement process of the chimney.